Designing an IPAS lesson plan with understanding by design approach for grade v elementary school - Vigo Pratama Saputra; Iin Purnamasari; Suyitno (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study presents the feasibility and validity of IPAS learning planning using the Understanding by Design (UbD) approach in a fifth-grade elementary school. This study uses a research and development (R&D) methodology that adopts the ADDIE model (Analyse, Design, Development, Implementation, and Evaluation). The data collection instruments were expert lecturer validity, teacher feasibility questionnaires, and student feasibility questionnaires, developed based on the review of the supervising lecturer and expert assessment. The implementation stage involved applying the developed learning plan to fifth-grade students at Karangsono 02 Public Elementary School. The trials at this stage included product validity and feasibility tests conducted by expert lecturers, classroom teachers, and fifth-grade students. The results show that the subject matter experts scored 91% in the excellent category, the learning planning experts scored 81% in the good category, and the teacher and student questionnaires were rated very feasible (93% and 87%). The evaluation stage included evaluations conducted at each stage of the ADDIE model. Data analysis techniques used triangulation. The results demonstrate that the IPAS learning plan, developed using the UbD approach, was valid and feasible for use in elementary schools, offering a valuable and innovative learning experience for teachers and students.